Ketamine metabolite pilot study in a suicidal depression trial. (October 2019) - Grunebaum, Michael F.; Galfalvy, Hanga C.; Choo, Tse-Hwei; Parris, Michelle S.; Burke, Ainsley K.; Suckow, Raymond F.; Cooper, Thomas B.; Mann, J. John
Abstract: Ketamine shows promise as a rapidly-acting treatment for depression and suicidal ideation, but side effects and abuse potential limit its use. Understanding its mechanism of action could help develop analogous but safer drugs. This post hoc study explored relationships of ketamine and metabolites, including hydroxynorketamine enantiomers, (2S, 6S)- and (2R, 6R)- HNK, to clinical response in a subgroup from a published trial in suicidal depression. Depressed adults with clinically significant suicidal ideation were randomized to double-blind infusion of sub-anesthetic ketamine or midazolam. Ketamine and metabolites were measured after infusion (N = 53). Plasma (2R, 6R) -HNK was associated with change (higher levels correlated with less clinical improvement) from baseline to 24 h post-infusion of depression (HDRS-24: Spearman r = 0.37, p = 0.009) and suicidal thoughts (SSI: Spearman r = 0.29, p = 0.041). There were similar correlations with weekly follow-up clinical rating scores for both HNK enantiomers and dehydronorketamine (DHNK). Ketamine and norketamine were not associated with change in depression or suicidal ideation (unadjusted p > 0.28).